Central motor commands to human elbow joint muscles during simultaneous changes in their force and length: a preliminary study - Gorkovenko, Andriy; Kolosova, Elena; Shushuiev, Dmytro; Maznychenko, Andriy; Kostyukov, Alexander (Frontiers in Physiology, 2026)
IntroductionMuscle hysteresis reflects nonlinear, history-dependent relationships between electromyographic (EMG) activity, muscle length, and force. Although hysteresis has been examined under fixed-length or fixed-force conditions, it remains unclear how EMG hysteresis behaves when muscle length and force change simultaneously, especially when their temporal patterns coincide or oppose each other. This preliminary study aimed to determine how a combination of simultaneous changes in the muscle force and length may influence the EMG hysteresis in elbow flexors.MethodsA robotic mechatronic device generated cyclic elbow movements while participants produced voluntary forces controlled through visual biofeedback. EMG hysteresis was quantified across various combinations of identical temporal patterns of the muscle length and force changes in form of a double trapezoid. Two patterns of the length changes were of the same amplitude range differing by direction of the movement phases: lengthening–shortening and shortening–lengthening. Each of the above length patterns were combined with five patterns of force change: two maximal amplitude of change, two half maximal amplitude, and one isotonic.ResultsEMG hysteresis was shaped not only by the direction of muscle length change but also strongly by the direction of the accompanying force change. Under isotonic conditions, EMG intensity increased during lengthening and decreased during shortening. With increasing the force amplitude changes in coinciding direction, the amplitude of EMG hysteresis, i.e., its difference between shortening and lengthening branches, increases, whereas with force changes in the opposing direction, it decreases significantly, even reaching negative values, thereby disrupting the usual direction of hysteresis effects.ConclusionThis study systematically demonstrates that muscle hysteresis can be significantly dependent on a combination of changes in muscle strength and length, as well as their history. The results open new perspectives for analyzing various problems in human motor control and movement rehabilitation.